2016
DOI: 10.1007/s00392-016-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

The wearable cardioverter-defibrillator in a real-world clinical setting: experience in 102 consecutive patients

Abstract: WCD therapy was well accepted by patients and provided temporary protection against ventricular tachyarrhythmias in patients at risk for SCD. The WCD may help to avoid unnecessary ICD implantations in a significant proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 21 publications
1
35
2
Order By: Relevance
“…ICD implantation rate in the whole patient cohort was 54%. This parallels other studies with similar patient collectives that reported implantation rates of 34 to 57% [ 9 , 14 , 16 , 21 , 22 ]. Naturally, ICD implantation rate was highest in the patient group with a prior explanted trans-venous ICD.…”
Section: Discussionsupporting
confidence: 90%
“…ICD implantation rate in the whole patient cohort was 54%. This parallels other studies with similar patient collectives that reported implantation rates of 34 to 57% [ 9 , 14 , 16 , 21 , 22 ]. Naturally, ICD implantation rate was highest in the patient group with a prior explanted trans-venous ICD.…”
Section: Discussionsupporting
confidence: 90%
“…Our data shows that patients with PPCM are facing a relevant risk for life-threatening arrhythmias in the first months after diagnosis. The WCD has shown to be effective in preventing sudden cardiac death in several other cardiomyopathies [12], especially post myocardial infarction and in non-ischemic cardiomyopathy [1315]. In the special setting of ICD removal due to infection, a WCD-guided strategy has been shown to be cost-effective [16].…”
Section: Discussionmentioning
confidence: 99%
“…None of these studies use implanted recorder to detect the arrhythmia recurrence which makes their estimation of AF recurrent rate suboptimal. For expense or non-invasive reason, wearable instrument which was usually used to avoid unnecessary ICD implantation might take as the substitution [ 54 ]. Testing studies on these scores with much precise recurrent AF rate may help to improve overcome this limitation.…”
Section: Introductionmentioning
confidence: 99%